What should regulators do about consolidation and electronic money? - Solomon, ElinorHarris (Journal of Banking & Finance, 1999)
Shared systems in the credit card mode may offer electronic money such as stored value (“smart”) cards, e-cash, and cybermoney. In such consolidations bank partners potentially may come from far outside the customary regulated banking fraternity. While some cyberbanks have been granted official status with its responsibilities, other nonbank cyberbanks have absconded with deposits amidst fraudulent claims. Electronic money is distributed typically in complex tiers, with backup reserves often held by nonbank third parties. The regulatory rules which apply to the mixed systems are therefore uneven and unclear. Banking regulators and the Antitrust Division wrestle with the ensuing dilemmas.